Narrow Band Imaging in Laryngeal Lesions:A Valuable Tool in Decision Making - Swaminathan, Deepa; Iype, Elizabeth M; Sharma, Anukampa; KM, Jagathnath Krishna; Varghese, Bipin T; Thomas, Shaji (Asian Pacific Journal of Cancer Care, 2024)
Objective: To assess the efficacy of Narrow band Imaging (NBI) in detecting laryngeal malignancies by statistical analysis. Methods: This prospective, observational study was conducted from 1st September 2022 to 31st December 2023. All patients above 18 years, who were scheduled to undergo nasopharyngolaryngoscopy with biopsy for laryngeal lesions, were included. Total 84 patients were included who were divided into two groups, Group A- with no previous treatment, Group B- with previous radiation to the larynx. They underwent routine white light endoscopy followed by NBI and grading was determined. Suspicious areas were biopsied and sent for histopathology. Based on the final report, the diagnostic accuracy was assessed using area under the curve (AUC) in ROC curve, sensitivity, specificity, Positive Predictive Value (PPV), Negative Predictive Value (NPV) and accuracy. Results: Group A included 54 patients. Thirty-five had a clearly malignant lesion on WLE, however NBI showed Grade IV IPCL pattern in three. The final histopathology in them showed squamous cell carcinoma (p value 0.019). One patient had vocal cord leukoplakia on WLE which showed Grade IV NBI pattern. The histopathology showed early squamous cell carcinoma. The remaining 18 had equivocal lesions on WLE with six showing Grade V NBI pattern. The final histopathology showed squamous cell carcinoma in five and moderate dysplasia in one (p value 0.574). Statistical analysis in Group A showed WLE had a sensitivity of 80.49% whereas NBI had 82.93 %. Specificity of WLE was 71.43% and NBI was 69.23%. Group B included 30 patients. Nineteen had malignant lesions on WLE. Of them 2 had Grade IV NBI pattern and one of them showed squamous cell carcinoma in histopathology (p value 1.000). Eleven patients had equivocal lesions in WLE and NBI in 6 showed Grade V pattern. Of these, four showed squamous cell carcinoma on histopathology, one had sarcoma and one showed mild to moderate dysplasia (p value 0.261). Statistical analysis showed WLE had a sensitivity of 69.23% while NBI had 88%. Specificity of WLE was 75% while NBI had 80%. Conclusion: We found that NBI in post irradiation setting, showed higher sensitivity and specificity. Hence it can aid in early detection of recurrent lesions that may otherwise be masked by treatment related changes.